2008
DOI: 10.1007/s00425-008-0860-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel type II cell wall architecture in dichlobenil-habituated maize calluses

Abstract: Growth of maize (Zea mays L.) callus-culture cells was inhibited using dichlobenil (2,6 dichlorobenzonitrile, DCB) concentrations > or =1 microM; I (50) value for the effect on inhibited fresh weight gain was 1.5 microM. By increasing the DCB concentration in the culture medium, DCB-habituated cells became 13 times more tolerant of the inhibitor (I (50): 20 microM). In comparison with non-habituated calluses, DCB-habituated calluses grew slower, were less friable and were formed by irregularly shaped cells sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 45 publications
6
55
1
1
Order By: Relevance
“…41 In this case, FTIR monitoring together with multivariate analysis showed not only a reduction in cellulose content in the cell walls of habituated cells, but also an increase in the signals corresponding to aromatic rings. These results were confirmed by other chemical analyses, such as gas and liquid chromatography, [41][42][43] showing a higher proportion of arabinoxylans cross-linked by phenolics in habituated cells. The analysis also showed that the modifications Figure 2.…”
Section: Discussionmentioning
confidence: 74%
“…41 In this case, FTIR monitoring together with multivariate analysis showed not only a reduction in cellulose content in the cell walls of habituated cells, but also an increase in the signals corresponding to aromatic rings. These results were confirmed by other chemical analyses, such as gas and liquid chromatography, [41][42][43] showing a higher proportion of arabinoxylans cross-linked by phenolics in habituated cells. The analysis also showed that the modifications Figure 2.…”
Section: Discussionmentioning
confidence: 74%
“…The ASF and AIF samples were freeze-dried after a dialysis step (molecular mass cutoff, 3,500 Da; Spectra/ Por; Spectrum Laboratories) against deionized water to remove solutes of a small molecular mass (the dialysis tubings were thoroughly washed before use to eliminate any contaminants potentially associated with the membranes). The presence of glycogen/starch-like polymers in the samples was ruled out by performing carbohydrate analyses at different steps of the fractionation procedure, before and after enzymatic hydrolysis in the presence of amylases (24). Since identical total sugar and glycosidic linkage profiles were obtained from all samples analyzed before and after enzymatic treatment, the amylase hydrolytic step was omitted in the final procedure to avoid the introduction of undesirable proteins in the cell wall extracts.…”
Section: Strainsmentioning
confidence: 99%
“…FT-MIR spectroscopy has been also applied in conjunction with PCA to monitor changes in the type II cell wall during habituation of maize cultures to DCB (Mélida et al, 2009). The FT-MIR spectra of walls of DCB-habituated cell lines showed differences in wavenumbers attributed to cellulose, phenolic components, arabinose, and proteins, with respect to non-habituated cells.…”
Section: Ft-mir Monitoring Of Cell Wall Changes Associated With Cbismentioning
confidence: 99%